Floating treatment islands in series along a channel: The impact of island spacing on the velocity field and estimated mass removal. (July 2019) - Liu, Chao; Shan, Yuqi; Lei, Jiarui; Nepf, Heidi
Highlights: For floating treatment islands (FTIs) in series, the velocity distribution in the root zone is fully developed by the third FTI. Mass removal by FTIs in series was predicted using a first-order removal model with rate constant k and residence time T within the root zone. For kT  ≥ 2, the maximum mass removal per channel length was achieved for FTI spacing Δ L  =  to L to 3 L, with root zone length L . For kT  ≤ 1, the maximum mass removal per channel length was achieved for FTI spacing Δ L  =  L to 2 L . Abstract: Floating treatment islands (FTIs) consist of emergent vegetation grown on floating structures. The submerged roots beneath the island and the biofilm they support filter nutrients and particulates from water passing through the roots. FTIs are often deployed in series within a channel, but an optimum spacing between FTIs has not yet been determined. The goal of the present study is to identify an optimum spacing for maximum mass removal per channel length. A series of scaled FTI models were deployed in a water channel with the spacing between FTIs ranging from 0.5 to 11 times the length of an individual root zone. A Nortek Vectrino was used to measure the velocity field to determine the flow rate into and residence time within each root zone. The measured flow distribution was used within a control volume analysis to estimate the mass removed per channel length, assuming that removal within the root zone followed a first-order reaction. As the spacing between the FTIs decreased, the flow entering each FTI root zone also decreased, which decreased the mass removed by each individual FTI. However, as the spacing between FTIs was decreased, the number of FTIs per channel length increased, which tended to increase the mass removal of the system of FTI in series. These competing trends produced a maximum mass removal for FTIs spaced between one and three times the root zone length. The maximum spacing was weakly dependent on the assumed first-order reaction rate. The present study can help designers choose an optimal spacing for FTIs in series to achieve the maximum mass removal per river length.